2022
DOI: 10.7759/cureus.29172
|View full text |Cite
|
Sign up to set email alerts
|

Regional Trends for the 2021 COVID-19 Independent Plastic Surgery Match Cycle

Abstract: Introduction: The coronavirus disease (COVID) created an abrupt change to virtual experiences and interviews for both the integrated and independent plastic surgery match cycle of 2021. Studies have shown that during the 2021 match cycle, integrated applicants were more likely to match at their home institution and region of medical school. These geographic and location trends for the 2021 match cycle have not been explored yet for the independent plastic surgery match.Methods: Information for independent plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 9 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…These trends were significant, which is a new finding relative to the prior study of only the 2019–2021 interview cycles. 21 For integrated programs, there was a transient increase in home program matches (25.12%) during the first COVID-19 cycle of 2021, which was higher than 2016–2020 and 2022 cycles’ home program match average (17.69%). 25 In contrast, independent program match trends did not transiently change during the 2021 cycle, and instead there is a sustained trend towards matching into a different region when interviews are virtual (2021–2023 cycles).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…These trends were significant, which is a new finding relative to the prior study of only the 2019–2021 interview cycles. 21 For integrated programs, there was a transient increase in home program matches (25.12%) during the first COVID-19 cycle of 2021, which was higher than 2016–2020 and 2022 cycles’ home program match average (17.69%). 25 In contrast, independent program match trends did not transiently change during the 2021 cycle, and instead there is a sustained trend towards matching into a different region when interviews are virtual (2021–2023 cycles).…”
Section: Discussionmentioning
confidence: 95%
“…20 However, when looking at those applying to the independent pathway, there was no significant change in match rate to home program or within the same region of the country in 2021 as compared with 2019 and 2020 pre-COVID-19 years. 21 This study expands upon this trend by including more virtual interview cycle years.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have investigated the effects of COVID-19 on changes in gender composition of the Match, but those studies that investigated this have found similar findings in plastic surgery as in our analysis, as well as a similar gender makeup overall. 14 This stagnation of the ratio of male-to-female applicants is particularly interesting given the recent push for an increase in women in neurosurgery. 15 , 16 Despite the efforts that have been made to increase female representation in neurosurgery, this stagnation may be due to a variety of factors, such as limited role models and mentorships for women or a lack of interest in the career due cultural and institutional factors, such as limited support for work-life balance or an absence of initiatives specifically targeting gender diversity with the specialty.…”
Section: Discussionmentioning
confidence: 99%
“…3 Recent studies demonstrated geographic biases in the PS match, with an increase in students matching to their home programs in the 2021 match following clinical and interview limitations in the setting of the COVID-19 pandemic. [4][5][6][7][8] Lack of affiliated residency programs is associated with less academic mentorship, fewer clinical exposures, and difficulty obtaining relevant letters of recommendation. 1,3,9 However, to our knowledge, no study investigated the association of individual medical school's level of PS clinical exposure with their student match rate in this specialty.…”
mentioning
confidence: 99%
“…A prior analysis of 2016 to 2021 PS matches demonstrated that medical students from schools with affiliated integrated PS residency programs comprised about 72% of PS matches, while those from allopathic schools without affiliated programs comprised about 24%; osteopathic and international medical graduates made up less than 5% of PS matches 3 . Recent studies demonstrated geographic biases in the PS match, with an increase in students matching to their home programs in the 2021 match following clinical and interview limitations in the setting of the COVID-19 pandemic 4–8 . Lack of affiliated residency programs is associated with less academic mentorship, fewer clinical exposures, and difficulty obtaining relevant letters of recommendation 1,3,9 .…”
mentioning
confidence: 99%